2021
DOI: 10.1039/d1ob00341k
|View full text |Cite
|
Sign up to set email alerts
|

Selective sensing of adenosine monophosphate (AMP) over adenosine diphosphate (ADP), adenosine triphosphate (ATP), and inorganic phosphates with zinc(ii)-dipicolylamine-containing gold nanoparticles

Abstract: Mixed monolayer-protected gold nanoparticles containing surface-bound triethylene glycol and dipicolylamine groups aggregated in water/methanol, 1:2 (v/v) in the presence of nucleotides, if the solution also contained zinc(II) nitrate to convert...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…[4][5][6][7] Pyrophosphate, a by-product of cellular hydrolysis of ATP, plays a crucial role in energy transduction, DNA polymerization, and several major metabolic processes. [8][9][10] However, the over-use of inorganic phosphates in agriculture can lead to unrestrained algal growth, followed by the breakdown and exhaustion of dissolved oxygen and, eventually, the eutrophication of aquatic habitats. [11][12][13] Since pyrophosphate is significantly involved in DNA duplication and transcription, the concentration of intracellular pyrophosphate can provide important information on essential processes such as DNA replication and, therefore, can be used to monitor or diagnose a number of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Pyrophosphate, a by-product of cellular hydrolysis of ATP, plays a crucial role in energy transduction, DNA polymerization, and several major metabolic processes. [8][9][10] However, the over-use of inorganic phosphates in agriculture can lead to unrestrained algal growth, followed by the breakdown and exhaustion of dissolved oxygen and, eventually, the eutrophication of aquatic habitats. [11][12][13] Since pyrophosphate is significantly involved in DNA duplication and transcription, the concentration of intracellular pyrophosphate can provide important information on essential processes such as DNA replication and, therefore, can be used to monitor or diagnose a number of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…At first, we have synthesized a surfactant (C 16 DPA.Zn 2 + ) having head group of dipicolylamine bound zinc complex which is known for its selective recognition property and also has been utilized for generating dynamic self-assembly in previous literature reports (see also supporting information (SI)). [15][16][17] Surfactant or nanoparticle having self-assembled monolayer with outer surface containing headgroup complexed with Zn 2 + , ions for example triazacyclononane has been used for the hydrolysis of HPNPP. [14] It has been shown that substrate, like HPNPP by using its phosphate ion can induce assembly of a Zn 2 + ion as headgroup containing surfactant for its own hydrolysis in a co-operative fashion.…”
Section: Resultsmentioning
confidence: 99%
“…However, receptors capable of targeting AMP selectively are very rare. [27][28][29] Indeed, most reported nucleoside phosphate receptors exhibit a selectivity prole that is governed predominantly by electrostatic interactions and thus follows the order ATP > ADP > AMP. 6,8,[30][31][32] Such receptors are not suitable for detecting AMP during enzyme reactions, especially in the presence of ATP.…”
Section: Introductionmentioning
confidence: 99%